(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The sustained fast economic growth since the nineties has ensured that the private sector has grown leaps and bounds, making significant contributions to the GDP of the country in all the three sectors of economy namely - Agriculture, Manufacturing, and Services. The professionalization of the private sector, to be on par with the best companies in the world, has created a demand for managers who are well trained in handling all aspects of a business, be it Finance, Marketing, HR, Operations, etc. Keeping in mind this robust demand for trained managers, the Government of India encouraged the establishment and growth of Management Institutes and B-Schools and brought such institutions under the aegis of the All India Council for Technical Education (AICTE). According to the latest AICTE data for 2017-18, there were 3232 institutes in India offering post graduate programs in Management and the total approved intake for 2017-19 was 3,93,035 seats.The mushrooming of institutions offering post graduate programs in management (either an MBA degree or a Post Graduate Diploma in Management), has led to a problem of a different kind altogether – employability of the management students. As per most reports released by government agencies and industry bodies, the employability of management students is pathetically low at less than 10. This empirical based research paper tries to look at the factors that influence the employability of management students. For the purpose of gathering the empirical data, students from two management institutions in Bangalore were surveyed through a questionnaire, and the results have been analysed and presented in the research paper.